2019
DOI: 10.1111/ecog.04485
|View full text |Cite
|
Sign up to set email alerts
|

Temporal partitioning of activity: rising and falling top‐predator abundance triggers community‐wide shifts in diel activity

Abstract: Top predators cause avoidance behaviours in competitors and prey, which can lead to niche partitioning and facilitate coexistence. We investigate changes in partitioning of the temporal niche in a mammalian community in response to both the rapid decline in abundance of a top predator and its rapid increase, produced by two concurrent natural experiments: 1) the severe decline of the Tasmanian devil due to a transmissible cancer, and 2) the introduction of Tasmanian devils to an island, with subsequent populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 55 publications
2
44
0
Order By: Relevance
“…In addition to predation pressure, energetic state influences an animal's GUD (Brown 1992, Bedoya-Perez et al 2013. Other research shows that devils modify the behaviour of mesopredators and prey; for example, spotted-tailed quolls Dasyurus maculatus temporally partition activity to avoid devils at high density (Cunningham et al 2019a), and feral cats Felis catus willingly feed on carcasses in areas where devils are rare, but less so in areas where devils are abundant, possibly a response to increased risk of encountering a devil at a carcass (Cunningham et al 2018). Maria Island and the control region were both exposed to similarly low rainfall preceding the 'after' period, yet the control region saw a significantly larger drop in GUDs, and the two regions had significantly different slopes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to predation pressure, energetic state influences an animal's GUD (Brown 1992, Bedoya-Perez et al 2013. Other research shows that devils modify the behaviour of mesopredators and prey; for example, spotted-tailed quolls Dasyurus maculatus temporally partition activity to avoid devils at high density (Cunningham et al 2019a), and feral cats Felis catus willingly feed on carcasses in areas where devils are rare, but less so in areas where devils are abundant, possibly a response to increased risk of encountering a devil at a carcass (Cunningham et al 2018). Maria Island and the control region were both exposed to similarly low rainfall preceding the 'after' period, yet the control region saw a significantly larger drop in GUDs, and the two regions had significantly different slopes.…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrate that top predators modify the behaviour of prey by instilling fear, and that behavioural change can occur rapidly following top predator introductions, far more rapidly than demographic change. Other research shows that devils modify the behaviour of mesopredators and prey; for example, spotted-tailed quolls Dasyurus maculatus temporally partition activity to avoid devils at high density (Cunningham et al 2019a), and feral cats Felis catus willingly feed on carcasses in areas where devils are rare, but less so in areas where devils are abundant, possibly a response to increased risk of encountering a devil at a carcass (Cunningham et al 2018). The next important step is to quantify how these behavioural changes affect fitness, demography and the flow-on effects to vegetation.…”
Section: Discussionmentioning
confidence: 99%
“…Other research shows that devil declines have resulted in the behavioural release of quolls. For instance, where devils are rare, quolls consume more carrion (Cunningham et al ) and increase their activity during the period of the day preferred by devils (Cunningham et al ). Despite this behavioural release, no study has found evidence for increased abundance of quolls following devil declines (Hollings et al ; Troy ; Hollings et al ), and our study further supports those findings.…”
Section: Discussionmentioning
confidence: 99%
“…For example, possums relaxed their risk-sensitive foraging behaviours following devil population declines (Hollings et al 2015), and reinstated these behaviours following the introduction of devils to the previously devil-free Maria Island (Cunningham et al 2019a). Wallabies also responded to the introduction of devils to Maria Island by increasing activity at periods of the day when devils are inactive (Cunningham et al 2019c). Because possums are typically arboreal but often forage on the ground, the trends we show here could reflect changes in abundance or increased ground-based activity by possums in response to a relaxed landscape of fear (Hollings et al 2015;Cunningham et al 2019a).…”
Section: Discussionmentioning
confidence: 99%
“…In quolls, home range size varies from several hundred to several thousand hectares, and while male home ranges overlap females are intrasexually territorial but tolerate the presence of female young (Belcher & Darrant 2004; Claridge et al 2005; Glen & Dickman 2006b). A recent camera study revealed temporal shifts in quolls in response to progressive decline in devil populations across the width of Tasmania, suggesting temporal avoidance by quolls of devils (Cunningham et al 2019).…”
Section: Introductionmentioning
confidence: 99%